2019
DOI: 10.1007/978-3-030-35333-9_29
|View full text |Cite
|
Sign up to set email alerts
|

What’s Hot in Product Roadmapping? Key Practices and Success Factors

Abstract: Context: Organizations are increasingly challenged by dynamic and technical market environments. Traditional product roadmapping practices such as detailed and Ąxed long-term planning typically fail in such environments. Therefore, companies are actively seeking ways to improve their product roadmapping approach. Goal: This paper aims at identifying problems and challenges with respect to product roadmapping. In addition, it aims at understanding how companies succeed in improving their roadmapping practices i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A recent review of the scientific literature about product roadmaps has shown that most scientific articles do not address product roadmaps operationally or refer to modern product management practices [ 5 ]. Furthermore, an initial review of the grey literature on product roadmapping in general and the conduction of expert interviews [ 4 , 12 ] indicate that the topic product roadmap alignment is highly relevant and of great interest for practitioners. In order to obtain more insights, the conduction of a grey literature review is an appropriate approach and contributes to the transfer of practical knowledge in the scientific community.…”
Section: Research Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of the scientific literature about product roadmaps has shown that most scientific articles do not address product roadmaps operationally or refer to modern product management practices [ 5 ]. Furthermore, an initial review of the grey literature on product roadmapping in general and the conduction of expert interviews [ 4 , 12 ] indicate that the topic product roadmap alignment is highly relevant and of great interest for practitioners. In order to obtain more insights, the conduction of a grey literature review is an appropriate approach and contributes to the transfer of practical knowledge in the scientific community.…”
Section: Research Approachmentioning
confidence: 99%
“…Thereby, individual goals are often placed above corporate goals. As a result, not every product activity contributes to achieving the company’s vision and goals, thus wasting important organizational resources [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%